PENDAMPINGAN PEMANFAATAN PEKARANGAN RUMAH PERKOTAAN MELALUI BUDIDAYA PADI DALAM POLYBAG - Paiman, Paiman; Tri Kusumastuti, Cicilia; Ardiyanta, Ardiyanta (Jurnal Berdaya Mandiri, 2024)
The area of agricultural land around urban areas is getting smaller due to conversion to residential expansion which can no longer be controlled. Rice cultivation can also be done in polybags placed in the yard. The community service is entitled "Assistance in the use of urban residential yards through cultivation in polybags". The service was carried out in the Agroshop garden, Faculty of Agriculture, PGRI University Yogyakarta. This service aims to develop productive economic activities of farmers through cultivating rice in polybags for use in home gardens in urban settlements. The service method is carried out through counseling activities, training and rice cultivation practices including making planting media, planting, maintaining and harvesting. The results of the service showed that 60 polybags with a size of 40 x 40 cm had been filled with planting media. The average rice yield per polybag is 150 g of milled dry grain per clump. The service findings show that rice cultivation in polybags has great potential to be developed in urban residential yards in the context of national food self-sufficiency. Keywords: rice, polybag, residential yard, urban.